2018
DOI: 10.3389/fcvm.2018.00063
|View full text |Cite
|
Sign up to set email alerts
|

Screening For Pulmonary Hypertension With Multidetector Computed Tomography Among Patients With Severe Aortic Stenosis Undergoing Transcatheter Aortic Valve Implantation

Abstract: Aim: To assess the accuracy of multi-detector computed tomography (MDCT) derived pulmonary vessel measurements in predicting pulmonary hypertension (PH) among patients with severe symptomatic aortic stenosis (AS) undergoing transcatheter aortic valve implantation (TAVI).Background: PH is common among patients with severe AS undergoing TAVI and is associated with adverse outcomes. MDCT is the imaging modality of choice to assess anatomical dimensions among patients selected for TAVI.Methods: One hundred and thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Additionally, CT angiography is utilized to gain information about the great arteries and aortic valve annulus of every patient undergoing TAVR. As per current European Society of Cardiology (ESC) guidelines [ 10 ], CT imaging may be used to assess PH in a non-invasive manner [ 11 , 12 ]. Pulmonary artery diameter/body surface area (PA/BSA), with a cut-off value of 16.6 mm/m 2 , was used in this study to possibly diagnose PH.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, CT angiography is utilized to gain information about the great arteries and aortic valve annulus of every patient undergoing TAVR. As per current European Society of Cardiology (ESC) guidelines [ 10 ], CT imaging may be used to assess PH in a non-invasive manner [ 11 , 12 ]. Pulmonary artery diameter/body surface area (PA/BSA), with a cut-off value of 16.6 mm/m 2 , was used in this study to possibly diagnose PH.…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of studies use PASP as a key component of PH evaluation. O'Sullivan et al [25] tested computed tomography for PH evaluation and proposed the ratio of the diameter of the main pulmonary artery to the diameter of the ascending aorta as best correlating with PASP. In patients with PA/AA ratio >0.80, PH is more likely, however, PH cannot be reliably excluded among patients with lower PA/AA ratio values.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasted with the statement of Turner et al [53], who found a relevant association with respect to 1-year survival, particularly in the complex calculation of MPA area. O'Sullivan et al [54] used a similar patient population as Eberhard et al (TAVR patients with RHC data as well as multi-detector computed tomography (MDCT) measurements). The results showed not only significantly higher MPA Diameter and PA/AA ratios in PH patients, but also good correlation analyses with corresponding right heart catheterization data.…”
Section: Echocardiographymentioning
confidence: 99%